ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI MANAJEMEN LABA (Studi Empiris Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2016-2017) - Hafiz Gavra Niranda; Dul Muid (Diponegoro Journal of Accounting, 2020)
In the financial statements, management often manipulates the numbers so that it shows the company's performance as if good, even though the company is actually not in good condition. Management does this so that investors continue to trust and attract other investors to want to invest in the company. The behavior called earnings management is a deviation in the financial statements carried out by management, one of which concerns the level of earnings presented in the financial statements. The purpose of this study is to examine whether earnings management is influenced by several factors such as previous year's earnings performance, audit quality, audit committee, and firm size. The control variable of this study uses absolute total accruals, return on assets, investments, and cash flow operations. The sample used in this study was 190 annual financial reports from 95 manufacturing companies listed on the Indonesia Stock Exchange in 2016-2017. The method used for this research is purposive sampling. The results of this study indicate that the audit quality has a significant negative effect on earnings management, and the audit committee has a significant positive effect on earnings management. While the previous year’s earnings performance has not a significant positive effect on earnings management, and the firm size has not a significant positive effect on earnings management.